Two Cases of Ectopic Hamartomatous Thymoma Masquerading as Sarcoma - Takahito Kondo; Yukiko Sato; Hiroko Tanaka; Toru Sasaki; Kazuyoshi Kawabata; Hiroki Mitani; Hiroyuki Yonekawa; Hirofumi Fukushima; Wataru Shimbashi (Case Reports in Otolaryngology)
Ectopic hamartomatous thymoma (EHT) is an extremely rare benign tumor. EHTs are difficult to differentiate from sarcomas, especially synovial sarcomas. We encountered two cases of EHT that were referred from other hospitals because sarcoma was suspected. In these cases, fusion gene detection via polymerase chain reaction or fluorescence in situ hybridization was useful for differentiating EHT from synovial sarcoma. EHT requires accurate diagnosis before surgery to avoid excessive treatment. Both tumor location and the presence of fat inside the tumor are important imaging findings for EHT, and confirmation of spindle cells, epithelial cells, and mature adipose cells in the tumor is an important pathological finding. It is important to exclude synovial sarcoma from the differential diagnosis via fusion gene analysis.